The effect of oxygen partial pressure on dislocation creep in polycrystalline uranium dioxide. Issue 3 (March 2021) - Garcia, Philippe; Miard, Audrey; Helfer, Thomas; Parise, Jean-Baptiste; Iltis, Xavière; Antou, Guy
Abstract: We report a set of compression test experiments carried out on sintered uranium dioxide at 1500 ° C, at constant strain rates and under controlled oxygen partial pressures. The macroscopic data indicate an initial strain hardening stage followed by a quasi steady-state period during which changes in the stress level are sluggish. The data are further interpreted in a continuum mechanics, finite strain framework, in both one and two-dimensional geometries, whence stress and oxygen partial pressure exponents of the creep law are estimated. The stress exponent is indicative of power-law creep. The oxygen partial pressure exponent is consistent with a strain-rate limited by vacancy mediated self-diffusion of the slowest moving ion, suggesting a climb-controlled recovery process. Some samples are further characterized using SEM/EBSD which reveals signs of plastic deformation typical of recovery creep. The effect of oxygen pressure upon microstructure is discussed.